Perception towards Online MCQ Test for MBBS and BDS Students’ As an Assessment Method during the Covid-19 Pandemic - Rajeshwar Reddy Kasarla; Naziya Khatoon; Chet Kant Bhusal; Nitasha Sharma; Snigdha Shubham; Laxmi Pathak (Journal of Universal College of Medical Sciences, 2022)
INTRODUCTION Universal College of Medical Sciences, Nepal conducted online multiple choice question test as a formative assessment method during COVID-19 pandemic. The aim of this study was to assess the MBBS and BDS students’ perception towards online assessment test conducted during COVID-19 lock down period. MATERIAL AND METHODS A descriptive, cross-sectional study was conducted on medical and dental students by administering online Google Forms questionnaire among 1st year and 2nd year MBBS and BDS students at Universal College of Medical Sciences, and College of Dental Surgery, during 2 October, 2021 to 30 December, 2021. General information proforma that elicits the socio-demography and a questionnaire on the lines of Likert’s summated rating scale to assess the perception of MBBS and BDS students towards online assessment test was constructed. The collected data were entered into Microsoft excel and exported to SPSS version 22 for analysis. Simple frequency tables, cross tables and standard deviation have been used to analyze data. RESULTS The overall mean and standard deviation for medical students’ perception of online assessments were 3.17 ± 0.65, respectively. Dental students’ perception of online assessment tests had an overall mean and standard deviation of 3.31 ± 0.77, respectively. There was no signiﬁcant difference in mean perception score towards online assessment test between the MBBS and BDS students (p value 0.1401). The results indicate that both medical and dental students were satisﬁed with online assessment tests. CONCLUSION Online assessment tests were well received by both MBBS and BDS students. The online assessment tests enhance student learning by allowing immediate feedback. Online tests should be conducted in MBBS and BDS colleges on a regular basis.